Return of the emerald skull - Stewart, Paul, 1955- (Stewart, Paul, 1955- Barnaby Grimes., 2009)
Weird and evil events at a London boarding school provide messenger Barnaby Grimes an opportunity to test his budding knowledge of the ancient Chinese art of yinchido, in which one focuses on silences and empty spaces.